Mengungkap Pemahaman Konsep Listrik Dinamis di Sekolah Berbasis Kemaritiman - Setiawan, Doni (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2019)
This study aims to describe the understanding of students' concepts on dynamic electric metrics in maritime-based schools in the city of Tegal. The study was conducted through a four-stage diagnostic test. The concept of dynamic electricity includes: Electric current strength, potential difference, series-parallel circuit, electric power, and Kirchoff's 1 law. The study was conducted at Tegal Nahdlatul Ulama High School as a sample of maritime-based schools in Tegal in the 2018/2019 school year. The sample used in the study was 29 students of class XII IPA Nahdlatul Ulama High School in Tegal city. The stages of research include (1) Reviewing references and journals related to understanding concept research; (2) Reviewing the syllabus to obtain misconceptions in the material of dynamic electric chapter physics; (3) Designing a question instrument in the form of a four tier test that can diagnose student misconceptions; (5) Validation by experts, namely with lecturers; (6) Test instruments to determine validity, reliability, degree of difficulty and differentiation of questions; (7) Test of student misconceptions carried out to students of class XII IPA at Nahdlatul Ulama High School. The results of data analysis obtained a description of students' understanding which could be categorized as understanding concepts, misconceptions, not understanding concepts and errors.